Pet attachment and prosocial attitude toward humans: the mediating role of empathy to animals - Faner, Jhon Marc V.; Dalangin, Ethel Ann R.; De Leon, Lei Ann Trishia C.; Francisco, Levi D.; Sahagun, Yessamin O.; Acoba, Evelyn F. (Frontiers in Psychology, 2024)
Attachment relationships are widely recognized as influential in increasing prosocial tendencies, with existing literature indicating that human attachment can increase empathetic processes, thereby potentially facilitating prosocial behavior. Given that pets frequently fulfill the criteria for attachment figures, this study investigates whether the observed associations among human attachment, empathy, and prosocial attitudes extend to human-animal interactions (HAI). This study examines the relationship between pet attachment, animal empathy, and prosocial attitudes towards humans. The study hypothesizes that animal empathy mediates the association between pet attachment and prosocial attitudes. A cross-sectional survey was administered to 343 Filipino participants, predominantly consisting of single female young adults with college education backgrounds. Participants completed a battery of assessments including the Contemporary Companion Animal Bonding Scale (CCABS), the Animal Empathy Scale (AES), and the Prosocialness Scale for Adults (PSA). Aligned with our hypothesis, our study reveals that animal empathy plays a significant mediating role in the relationship between pet attachment and attitudes towards humans. We found that stronger pet attachment correlates positively with heightened animal empathy, subsequently leading to elevated levels of prosocial attitudes. Our findings prompt discussions on implications for understanding human-animal relationships and suggest avenues for future research exploration.